Applied Linguistics: Language in its social context (Texas Journal of Philology, Culture and History, 2022)
Discussions of language in social contexts focus on language acquisition and language learning, the importance of language in communities, and the relationship between language and society. Language acquisition is distinguished from language acquisition. The former is performed unconsciously by the language user, while the latter is performed consciously by the language user. Language importance in the community is considered in terms of language importance in the community. And it is discussed in terms of three indivisible elements of community: human, community and language. Collaboration between members of social groups works well through the use of a means of communication called language. Language allows people to communicate their thoughts and desires to others, such as when they need help. Close cooperation takes place between members of the group